2020
DOI: 10.1111/anu.13054
|View full text |Cite
|
Sign up to set email alerts
|

Use of Artemia supplemented with exogenous digestive enzymes as sole live food increased survival and growth during the larviculture of the longsnout seahorse Hippocampus reidi

Abstract: This study evaluated the effect of exogenous digestive enzymes on the survival, growth performance and morphology of the digestive tract of juveniles of the longsnout seahorse Hippocampus reidi fed exclusively with Artemia and supplemented with five different concentrations of porcine pancreatin (PP) (0, 5, 25, 50 and 75 mg/L from birth until 30 days after release). The results found in the present study clearly show that there was a significant increase in survival and growth as well as substantial changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…The high survivals achieved in 7 DAR juveniles released by breeders fed on non-enriched Artemia (group M0) were similar or higher than previously reported in breeders fed on a high quality diet (Olivotto et al, 2008;Hora et al, 2017;Randazzo et al, 2018;de Souza et al, 2020).…”
Section: Reproduction Successsupporting
confidence: 81%
“…The high survivals achieved in 7 DAR juveniles released by breeders fed on non-enriched Artemia (group M0) were similar or higher than previously reported in breeders fed on a high quality diet (Olivotto et al, 2008;Hora et al, 2017;Randazzo et al, 2018;de Souza et al, 2020).…”
Section: Reproduction Successsupporting
confidence: 81%
“…nauplii followed by a combination of Artemia nauplii and Tisbe spp copepodites/copepods had the best survival, and weight and height growth. However, using solely Artemia without exogenous digestive enzymes and HUFAs supplement to feed H. reidi larvae showed poor results (Novelli et al., 2016; Randazzo et al, 2018; Souza et al., 2020). As seahorse larvae, Artemia is also considered to be lower nutritional value, especially in fatty acid, and presenting lower digestibility for juvenile at the age around 15–30 days old (Pham & Lin, 2013; Randazzo et al., 2018; Souza et al., 2020; Willadino et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, using solely Artemia without exogenous digestive enzymes and HUFAs supplement to feed H. reidi larvae showed poor results (Novelli et al., 2016; Randazzo et al, 2018; Souza et al., 2020). As seahorse larvae, Artemia is also considered to be lower nutritional value, especially in fatty acid, and presenting lower digestibility for juvenile at the age around 15–30 days old (Pham & Lin, 2013; Randazzo et al., 2018; Souza et al., 2020; Willadino et al., 2012). In this study, the widely used foods, frozen mysid shrimp (Hora & Joyeux, 2009) and frozen adult Artemia were fed, individually or combination, to H. reidi (2.5 months old), and results showed that superior growth performance and feed efficiency were recorded in seahorses fed frozen mysid shrimp (MD) for 56 days compared to that of seahorses fed frozen adult Artemia (AD) and the mixture (MAD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation